Authentic learning environments in higher education - Herrington, Anthony, 1950-; Herrington, Jan. (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2006)
"This book is made up of a collection of peer-reviewed chapters that reflect the construct of authentic learning--learning that is centred on rich, real-world, immersive and engaging tasks"--Provided by publisher.